Electrochemical Noise Measurements of Advanced High-Strength Steels in Different Solutions - Montoya Rangel, Marvin; Garza Montes de Oca, Nelson Federico; Gaona Tiburcio, Citlalli; Colás Ortíz, Rafael; Cabral Miramontes, José Ángel; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Chacón Nava, José G.; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2020)
Advanced high-strength steels (AHSS), are commonly used in the manufacture of car bodies, as well as in front and rear rails, and safety posts. These components can be exposed to corrosive environments for instance, in countries where de-icing salts are used. In this work, the corrosion behavior of four AHSS steels with dual-phase [ferrite-martensite (DP) and ferrite-bainite (FB)] steels were studied by means of electrochemical noise (EN) measurements according to the ASTM G199-09 standard in NaCl, CaCl2 and MgCl2 aqueous solutions at room temperature. The direct current (DC) trend data from EN were removed by a polynomial method of statistical and spectral analysis. According to the noise resistance (Rn) values obtained for the DP and FB dual-phase steels, both the martensite/bainite content and morphology of the phase constituents have an important effect on the corrosion behavior of these steels. The L.I. (localization index) (0.00054 to 0.15431), skewness (−6.18 to 7.35) and kurtosis (high values 37.15, 74.84 and 106.52) were calculated. In general, the results indicated that the main corrosion process is related to uniform corrosion. Corrosion behavior of AHSS steels exposed in NaCl solution could be related to the morphology of the phase constituents exposed in NaCl, CaCl2 and MgCl2 solutions.